The Psychological Symptoms and Difficulties Experienced By Parents of Children with Autism (Bangladesh Journal of Medical Science, 2024)
Objective: This study investigated the psychological symptoms and difficulties experienced by parents of children with autism.Method: This descriptive and cross-sectional study was conducted between November 2021 and June 2022. The sample consisted of 218 parents of children aged 3-18 living in XX. The sample was divided into two: 110 parents of children with autism and 108 parents of healthy children.Results: Parents of children with autism had a mean age of 36.15±6.142, while parents of healthy children had a mean age of 36.65±7.057. More than half of the parents of children with autism stated that they worried about their children’s future and had difficulty taking care of other children of theirs, making time for themselves, and maintaining daily life. On the other hand, only a quarter of the parents of healthy children stated that they worried about their children’s future and had difficulty taking care of other children of theirs, making time for themselves, and maintaining daily life. Parents of children with autism had a significantly higher mean anxiety, depression and hostility subscale score than parents of healthy children (p